2014
DOI: 10.1002/aoc.3175
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable 1,2‐bis[3,5‐bis(trifluoromethyl)phenyl]diselane‐catalyzed oxidation of cyclohexene with H2O2: a practical access to trans‐1,2‐cyclohexanediol

Abstract: 1,2-Bis[3,5-bis(trifluoromethyl)phenyl]diselane-catalyzed oxidation of cyclohexene by hydrogen peroxide affords a quick, clean and practical access to the important compound trans-1,2-cyclohexanediol under mild conditions. The highly atom-economic properties, clean procedures, high reaction concentration, short reaction time, mild conditions and eco-friendly, recyclable and low loading catalysts facilitate this methodology for possible future practical industrial production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 72 publications
(24 reference statements)
1
29
1
1
Order By: Relevance
“…This was attributed to the presence of a side non-catalyzed reaction that in water can be controlled and thus avoided. The current catalytic species was investigated by NMR, evidencing a peak on 77 Se-NMR that clearly indicates an overoxidized species of selenium (1204 ppm) that was attributed to the peroxyseleninic acid and that, in light of the evidence reported later by Yu et al, could also be assigned to the corresponding peroxyanhydride [54].…”
Section: Water As An Alternative Medium For Organoselenium-catalyzed mentioning
confidence: 92%
See 2 more Smart Citations
“…This was attributed to the presence of a side non-catalyzed reaction that in water can be controlled and thus avoided. The current catalytic species was investigated by NMR, evidencing a peak on 77 Se-NMR that clearly indicates an overoxidized species of selenium (1204 ppm) that was attributed to the peroxyseleninic acid and that, in light of the evidence reported later by Yu et al, could also be assigned to the corresponding peroxyanhydride [54].…”
Section: Water As An Alternative Medium For Organoselenium-catalyzed mentioning
confidence: 92%
“…Later the same authors, comparing the reactivity of a number of selenium catalysts using the same methodology, found that 1,2-bis(3,5-bis(trifluoromethyl)phenyl)diselane was the most efficient in terms of yield and reaction rate. In addition, they demonstrate by NMR spectroscopy that in the reaction mechanism the oxygen transfer species, when the precatalyst was diphenyl diselenide, is peroxyseleninic acid [54] ( Figure 13). generated by an undesired ring opening reaction of the epoxide.…”
Section: Water As An Alternative Medium For Organoselenium-catalyzed mentioning
confidence: 97%
See 1 more Smart Citation
“…On this basis, we envisioned that the oxidative ring expansion of MCPs to cyclobutanones might be achieved by an organoselenium‐catalyzed method by using H 2 O 2 as the oxidant. The organoselenium‐catalyzed oxidation of simple alkenes by H 2 O 2 has already been reported, but its application to the ring expansion of MCPs is still unknown. Given that MCPs are highly active molecules with multiple reaction sites and that the produced cyclobutanones may also undergo further Baeyer–Villiger oxidation, selective oxidation by using the strong oxidant H 2 O 2 faces tremendous challenges (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…Organoselenium catalysts were commercially available or were prepared through known methods. Solvents were analytically pure (AR) and were directly used without any special treatment. All reactions were monitored by TLC.…”
Section: Methodsmentioning
confidence: 99%